Intra-leiomyoma massive hemorrhage after delivery - Manatsawee Manopunya (2018)
Massive bleeding into a uterine leiomyoma is an extremely rare cause of hypovolemic shock. Only one case of this life-threatening condition has been reported. Our patient was a 39-year-old woman who had a gradual growth of a subserous myoma throughout pregnancy and sudden rapid growth after cesarean section at 35 weeks of gestation. The rapid growth was due to intra-tumor massive bleeding and was associated with hypovolemic shock without evidence of external or intra-abdominal hemorrhage.We hypothesize that a rapid decrease in size of the uterus after delivery might have compressed the venous drainages, which were more vulnerable to occlusion than arterial blood flows, resulting in blood sequestration into the tumor leading to hypovolemia. © 2012 The Authors.